2020
DOI: 10.3390/ma13020254
|View full text |Cite
|
Sign up to set email alerts
|

Facile Aqueous-Phase Synthesis of Bimetallic (AgPt, AgPd, and CuPt) and Trimetallic (AgCuPt) Nanoparticles

Abstract: Multi-metallic nanoparticles continue to attract attention, due to their great potential in various applications. In this paper, we report a facile aqueous-phase synthesis for multi-metallic nanoparticles, including AgPt, AgPd, CuPt, and AgCuPt, by a co-reduction method within a short reaction time of 10 min. The atomic ratio of bimetallic nanoparticles was easily controlled by varying the ratio of each precursor. In addition, we found that AgCuPt trimetallic nanoparticles had a core-shell structure with an Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Another very important factor is the synthetic process that can favor the formation of one or the other phase kind dependent on synthesis conditions. I.e Tang et al [ 20 ] reported the formation of AgPt, AgPd, and CuPt alloy nanoparticles and AgCuPt core-shell structure with an Ag core and CuPt shell by a co-reduction method. Selective incorporation of Pt on the Ag/Au nanoparticles by successive reduction method was demonstrated by Thongthai et al [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another very important factor is the synthetic process that can favor the formation of one or the other phase kind dependent on synthesis conditions. I.e Tang et al [ 20 ] reported the formation of AgPt, AgPd, and CuPt alloy nanoparticles and AgCuPt core-shell structure with an Ag core and CuPt shell by a co-reduction method. Selective incorporation of Pt on the Ag/Au nanoparticles by successive reduction method was demonstrated by Thongthai et al [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The co-reduction method is a straightforward process since the reduction of three metal salts is carried out simultaneously. 99 Shi et al 100 fabricated Pt 53 Ru 39 Ni 8 trimetallic nanosponges using the co-reduction wet chemical method, using hydrogen bubbles from the hydrolysis of sodium borohydride as a dynamic template for the synthesis of the spongelike structure. The trimetallic nanosponges were prepared without support on a clean surface or additional organic solvent or seed (Fig.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…The chemical composition of the alloy was chosen under the assumption that this alloy had a high catalytic potential [13][14][15][16], as well as a high configurational entropy of mixing (∆S mik conf = 1.61 R) [17]. Previous research in the field of synthesis of multi-component noble nanoparticles represents the successful synthesis of bimetallic [18,19] and trimetallic nanoparticles from the initial aqueous solution. AgPd and AgPt are used to improve catalysis in H 2 O 2 generation, while Cu-based particles such as CuPt and AgCuPt have been observed to exhibit high catalytic activity in the electrochemical reduction in CO 2 [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in the field of synthesis of multi-component noble nanoparticles represents the successful synthesis of bimetallic [18,19] and trimetallic nanoparticles from the initial aqueous solution. AgPd and AgPt are used to improve catalysis in H 2 O 2 generation, while Cu-based particles such as CuPt and AgCuPt have been observed to exhibit high catalytic activity in the electrochemical reduction in CO 2 [19].…”
Section: Introductionmentioning
confidence: 99%